Causal Inference for Heterogeneous Data and Information Theory - Hlaváčková-Schindler, Kateřina (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The present reprint, "Causal Inference for Heterogeneous Data and Information Theory", is a special issue of Journal Entropy. This Special Issue belongs to the section "Information Theory, Probability, and Statistics". The reprint gathers thirteen original contributions of leading experts in the theory of causal inference, focusing namely on the utilization of instrumental variables in a causal model, estimation of average treatment effect, the role of interventions in causal models, graphical causal modeling, causal algebras, causal modeling using the theory of categories, temporal causal model, heterogeneous data, and information-theoretic approaches.